Managers' perception of Information Management (IM) and Knowledge Management (KM) and the role of information and knowledge managers - Abdul Karim, Nor Shahriza; Wan Salleh, Wan Salwati (2003)
This paper reports a study conducted to investigate the progression of information and knowledge management (KM) within the business organizations in Malaysia from the managers’ point of view. Among the objectives set are to identify the information requirements of managers, to identify the need for effective information management (IM) and information managers, and to identify the role and skill requirements of information and knowledge managers in the organizations. Using survey questionnaires and interviews, the findings provided rich and meaningful information about information requirements of managers and their overall perception of information and KM. The findings also revealed the important roles of information and knowledge managers and their desired competencies as perceived by the managers. Positive perception towards the establishment of a one-stop resource center or library was also reported. Overall, the findings may assist in the initial stage of effective IM and KM strategy by organizations, and in the development of curriculum for the IM program and the related management fields.